Geometric analysis of macronutrient selection in breeds of the domestic dog, Canis lupus familiaris - Hewson-Hughes, Adrian K.; Hewson-Hughes, Victoria L.; Colyer, Alison; Miller, Andrew T.; McGrane, Scott J.; Hall, Simon R.; Butterwick, Richard F.; Simpson, Stephen J.; Raubenheimer, David (Behavioral Ecology, 2013)
Although many herbivores and omnivores have been shown to balance their intake of macronutrients when faced with nutritionally variable foods, study of this ability has been relatively neglected in carnivores, largely on the assumption that prey are less variable in nutrient composition than the foods of herbivores and omnivores and such mechanisms therefore unnecessary. We performed diet selection studies in 5 breeds of adult dog ( Canis lupus familiaris ) to determine whether these domesticated carnivores regulate macronutrient intake. Using nutritional geometry, we show that the macronutrient content of the diet was regulated to a protein:fat:carbohydrate ratio of approximately 30%:63%:7% by energy, a value that was remarkably similar across breeds. These values, which the analysis suggests are dietary target values, are based on intakes of dogs with prior experience of the respective experimental food combinations. On initial exposure to the diets (i.e., when naive), the same dogs self-selected a diet that was marginally but significantly lower in fat, suggesting that learning played a role in macronutrient regulation. In contrast with the tight regulation of macronutrient ratios, the total amount of food and energy eaten was far higher than expected based on calculated maintenance energy requirements. We interpret these results in relation to the evolutionary history of domestic dogs and compare them to equivalent studies on domestic cats.